Assessment of lifeline hospitals in Metro Manila as part of disaster preparedness for a possible large magnitude earthquake - Cereno, Karl Arwen O.
The main purpose of this study is to identifY and assess the lifeline hospitals in Metro Manila for a possible large magnitude earthquake. Several scenario earthquakes were identified by the Metropolitan Manila Earthquake Impact Reduction Study (MMEIRS) that can pose great threat to the lives, properties, and economy of the city. Hospitals playa vital role in minimizing the inconveniences and casualties in the event of an earthquake. Lifeline networks and buildings, particularly hospitals and health facilities, shall be given special attention since they will be crucial in accommodating the needs of the people in the areas that will be affected by the seismic activity. The criteria that was used for identifYing the lifeline hospitals was based on the Authorized Bed Capacity (ABC) of hospitals and the scope of service that they can provide. The level preliminary assessment tool, the Rapid Condition Assessment Tool, developed by the University of the Philippines-Diliman, Institute of Civil Engineering, was used to assess low-rise to mid-rise reinforced-concrete frame hospital buildings. Recommendations for higher level assessment and immediate interventions and repairs were provided for each of the evaluated lifeline hospitals.